Indoor air quality evaluation in oncology units at two European hospitals: Low-cost sensors for TVOCs, PM2.5 and CO2 real-time monitoring. (November 2021) - Palmisani, Jolanda; Di Gilio, Alessia; Viana, Mar; de Gennaro, Gianluigi; Ferro, Andrea
Abstract: IAQ assessment is a priority in oncology units where high air quality standards must be guaranteed to protect vulnerable patients. To fill the existing knowledge gap on IAQ in oncology units, extensive monitoring campaigns were performed inside two European oncology units (Bari in Italy, 24th February 2018–31st July 2019; Barcelona in Spain, 18th July-26th November 2018) for high temporal resolution monitoring of total volatile organic compounds (TVOCs), fine particulate matter (PM2.5 ), CO2 and other environmental parameters. Selected low-cost sensors (Corvus IAQ monitor, Speck, ZyAura CO2 monitor) were deployed. Laboratory and field inter-comparison of PM sensors with scientific-grade reference instruments was performed. TVOCs, PM2.5 and CO2 temporal profiles clearly show a regular weekday pattern with concentration peaks in daytime hours associated with higher human occupancy in the wards for scheduled chemotherapy treatments. Human occupancy (human emission and walking-induced particle resuspension), the administration of pharmaceutical products and the use of disinfectants and cleaning products predominantly affected TVOCs and PM2.5 concentrations in oncology wards. Although PM sensors showed low to moderate correlation with reference instruments (R 2 = 0.34–0.66), this study provides additional evidence on their potential for inexpensive, real-time monitoring and detection of pollution events. Mitigation measures could be applied to improve IAQ in the investigated locations including more efficient scheduling, improved waiting room design and better ventilation strategies. Graphical abstract: Image 1 Highlights: IAQ assessment is a priority in oncology hospitals due to vulnerable patients. TVOCs, PM2.5 and CO2 real-time monitoring with low-cost sensors integrated system. Peak concentrations in hours of higher human occupancy for chemotherapy treatments. Human occupancy and disinfectant/cleaning products as main sources of TVOCs and PM2.5 Evidence on potentialities of low-cost sensors for airborne pollutants monitoring.